Kaji Optimasi Desain Cetakan Injeksi Moulding pada Unit Pengolahan Limbah Plastik Dinas Kebersihan dan Pertamanan Kota Banda Aceh - Masri Ibrahim; - Irwansyah; Eddi Safrizal (Jurnal Teknik Mesin Unsyiah, 2012)
High impact of product damage by injection molds process on polymer waste processing unit was seriously affected to quality and sustainability production. In this study effect of injection mold design was minimized by investigated and redesign injection molding system. The main equipments of injection molding system which is available at Unit Pengolahan Limbah Plastik Dinas Kebersihan dan Permanan Kota Banda Aceh are polymer waste cutting, splitting and cleaning devices and injection molding machine. According to observation conducted previously on current injection molding product and mold found that failure of product caused by mis-design of mould. Products defects occurred are sink mark, weld line and air trap. Mold-Flow software was used to modeling and simulating injection mold process. Based on simulation result and discussion found that defected products have been able minimized. By modifying sprue location and redesign mold, products defect minimized and injection pressure still remain to push polymer to mold inlet at range 0,72-0,48 Mpa